2010
DOI: 10.1099/vir.0.023242-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mucosal and systemic antibody and T-cell responses following prime-boost immunization with novel adjuvanted human immunodeficiency virus-1-vaccine formulations

Abstract: As sexual transmission of human immunodeficiency virus-1 (HIV-1) occurs via the mucosa, an ideal HIV-1 vaccine should induce both mucosal and systemic immunity. We therefore sought to evaluate the induction of mucosal responses using a DNA env prime–gp120 protein boost approach in which sequential nasal and parenteral protein administration was performed with two novel carbohydrate-based adjuvants. These adjuvants, Advax-M and Advax-P, were specifically designed for mucosal and systemic immune enhancement, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 85 publications
0
52
0
1
Order By: Relevance
“…Intranasally administered toxin adjuvants such as CT and Escherichia coli heat-labile toxin (LT) showed greater induction of inflammatory responses than ''parenteral adjuvants such as CpG oligodeoxynucleotides, polymerized liposomes, microparticles and interleukins.'' 106 However, these toxin adjuvants can also induce inflammatory responses in the facial nerves, as demonstrated in human intranasal HIV and TB vaccine trials in which subjects experienced transient Bell's Palsy after the use of detoxified LT. 107,108 In addition, CT was detected in brains of mice following intranasal CT administration and was thought to have migrated via retrograde neuronal transport through the olfactory neurons. [109][110][111] Newer adjuvants such as the carbohydrate formulations Advax-M 106 and chitosan derivatives 112,113 may provide alternative candidates for safe and effective intranasal adjuvants.…”
Section: Intranasal Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intranasally administered toxin adjuvants such as CT and Escherichia coli heat-labile toxin (LT) showed greater induction of inflammatory responses than ''parenteral adjuvants such as CpG oligodeoxynucleotides, polymerized liposomes, microparticles and interleukins.'' 106 However, these toxin adjuvants can also induce inflammatory responses in the facial nerves, as demonstrated in human intranasal HIV and TB vaccine trials in which subjects experienced transient Bell's Palsy after the use of detoxified LT. 107,108 In addition, CT was detected in brains of mice following intranasal CT administration and was thought to have migrated via retrograde neuronal transport through the olfactory neurons. [109][110][111] Newer adjuvants such as the carbohydrate formulations Advax-M 106 and chitosan derivatives 112,113 may provide alternative candidates for safe and effective intranasal adjuvants.…”
Section: Intranasal Vaccinationmentioning
confidence: 99%
“…106 However, these toxin adjuvants can also induce inflammatory responses in the facial nerves, as demonstrated in human intranasal HIV and TB vaccine trials in which subjects experienced transient Bell's Palsy after the use of detoxified LT. 107,108 In addition, CT was detected in brains of mice following intranasal CT administration and was thought to have migrated via retrograde neuronal transport through the olfactory neurons. [109][110][111] Newer adjuvants such as the carbohydrate formulations Advax-M 106 and chitosan derivatives 112,113 may provide alternative candidates for safe and effective intranasal adjuvants. Intranasal administration of viral vectors such as vaccinia, fowlpox, and adenovirus can result in viral infection and inflammation of the CNS through the same mechanism.…”
Section: Intranasal Vaccinationmentioning
confidence: 99%
“…При применении у мышей, крыс, морских свинок, кроликов, цыплят, собак, овец, обезьян, лошадей и верблюдов данный адъювант усиливал иммуногенность различных бел-ковых антигенов, выделенных из вирусных, бактериальных и протозойных патогенных микроорганизмов, токсинов, опу-холевых антигенов и аллергенов. Адъювант Advax™ усиливал иммуногенность вакцин, что было показано на моделях мы-шей, инфицированных вирусами гриппа H1N1 [21], японского энцефалита [22], лихорадки Западного Нила [14], гепатита В [23] и вирусом иммунодефицита человека [24]. Адъювантное действие Advax™ продемонстрировано также на моделях хорь-ков, зараженных вирусом гриппа птиц H5N1 [25], лошадей, инфицированных японским энцефалитом [26], и верблюдов, зараженных вирусом африканской конской чумы и сапа [27].…”
Section: фруктановые адъювантыunclassified
“…Consequently, the GNP-LLO 91-99 nanovaccine was combined with the novel polysaccharide nanoparticle adjuvant, Advax TM , an adjuvant derived from delta inulin microparticles that has previously been shown to be effective and safe in human trials of influenza and hepatitis B vaccines 19,20 and has been shown to induce robust CD4 C and CD8 C T-cell responses. 21,22 GNP-LLO 91-99 nanovaccines formulated with Advax TM had markedly enhanced T-cell immunogenicity and conferred listeriosis protection to levels previously only achieved with in vitro DC loaded vaccines. Notably, the frequency of activated DC doubled when Advax TM adjuvant was added to the nanovaccine, together with significantly increased IL-12 production.…”
Section: Novel Nanoparticle Vaccines For Listeriosismentioning
confidence: 99%